Experimental Guide for Compact Bow-Tie Femtosecond Solid-State Laser Development - Vinícius Pereira Pinto; Giovana Trevisan Nogueira; Fátima Maria Mitsue Yasuoka; Jarbas Caiado de Castro Neto (Photonics)
Bow-tie cavity configurations have gained significant attention due to their efficacy in facilitating stable resonator operation for applications requiring short pulse operation and high repetition rate pulses, offering versatility and reliability. While there is an extensive body of literature addressing the theoretical aspects and applications of this laser configuration, there exists a gap in practical insights and systematic approaches guidance pertaining to the development and precision alignment of this laser type. The paper achieves this by compiling a range of analytical and optimization techniques for the bow-tie cavity configuration and delineating the necessary steps for the optimization required for continuous wave operation. This ultimately leads to the attainment of the pulsed regime through the Kerr Lens Mode-locking technique, offering a detailed account of the development, optimization, and performance evaluation of a Ti:Sapphire femtosecond laser cavity, using dispersion-compensating mirrors to produce a low-energy pulse of 1 nJ, a high repetition rate of 1 GHz, and a short pulse duration of 61 fs. This work can be useful for researchers and engineers seeking to embark on the development of compact and high-performance femtosecond lasers for a spectrum of applications, encompassing biomedical imaging, laser-assisted surgery, spectroscopy, and optical frequency combs.